Investigating Stability Problems in Solid Waste Landfills - Gökçe Buse Güner Karaca; Şeyma Ordu; Ertuğrul Ordu (Doğal Afetler ve Çevre Dergisi)
One of today’s most pressing environmental issues is related to waste disposal, especially landfilling. The quality of groundwater has been seriously compromised due to improper storage methods. Problems related to human health and environmental pollution are more common in open dumps. These irregular disposal sites cause many disadvantages and serious health problems. For this reason, cases that caused slope failures in landfills have been examined. This study investigates stability issues related to solid waste landfills, focusing on the assessment of waste stability. The study includes analyses of slope failure cases in various landfills: Hekimbasi, Dona Juana, Gnojna Grora, Hiriya, Payatas, and Xerolakka. Using Plaxis 2D software, the data obtained from these analyses have been rigorously evaluated to determine the most appropriate landfill management strategies. Slope collapses in landfills are generally caused by unsuitable landfill design, lack of daily cover laying and waste compaction, inadequate waste segregation, insufficient leachate drainage and gas discharge, and excessive slope angle and height. The presence of one or more of these conditions can result in a decline in site stability. Instabilities are experienced in these areas where engineering controls are inadequate.